Barriers and facilitators to reducing low-value care for the management of low back pain in Iran: a qualitative multi-professional study - Seyedeh Yasamin Parvar; Parviz Mojgani; Kamran Bagheri Lankarani; Fereshteh Poursaeed; Leila Sadat Mohamadi Jahromi; Vinaytosh Mishra; Alireza Abbasi; Saeed Shahabi (BMC, 2024)
Abstract Introduction Low back pain (LBP) is a prevalent musculoskeletal disorder with a wide range of etiologies, ranging from self-limiting conditions to life-threatening diseases. Various modalities are available for the diagnosis and management of patients with LBP. However, many of these health services, known as low-value care (LVC), are unnecessary and impose undue financial costs on patients and health systems. The present study aimed to explore the perceptions of service providers regarding the facilitators and barriers to reducing LVC in the management of LBP in Iran. Methods This qualitative descriptive study interviewed a total of 20 participants, including neurosurgeons, physiatrists, orthopedists, and physiotherapists, who were selected through purposive and snowball sampling strategies. The collected data were analyzed using the thematic content analysis approach. Results Thirty-nine sub-themes, with 183 citations, were identified as barriers, and 31 sub-themes, with 120 citations, were defined as facilitators. Facilitators and barriers to reducing LVC for LBP, according to the interviewees, were categorized into five themes, including: (1) individual provider characteristics; (2) individual patient characteristics; (3) social context; (4) organizational context; and (5) economic and political context. The ten most commonly cited barriers included unrealistic tariffs, provider-induced demand, patient distrust, insufficient time allocation, a lack of insurance coverage, a lack of a comprehensive referral system, a lack of teamwork, cultural challenges, a lack of awareness, and defensive medicine. Barriers such as adherence to clinical guidelines, improving the referral system, improving the cultural status of patients, and facilitators such as strengthening teamwork, developing an appropriate provider-patient relationship, improving the cultural status of the public, motivating the patients, considering an individualized approach, establishing a desirable payment mechanism, and raising the medical tariffs were most repeatedly stated by participants. Conclusion This study has pointed out a great number of barriers and facilitators that shape the provision of LVC in the management of LBP in Iran. Therefore, it is essential for relevant stakeholders to consider these findings in order to de-implement LVC interventions in the process of LBP management.